2022
DOI: 10.2147/cmar.s373379
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Cervical Cancer Patients During Follow-Up Care in Ethiopia: A Qualitative Study

Abstract: The purpose of the study was to explore the experiences among cervical cancer patients during follow-up care. Patients and Methods: A qualitative study was conducted with purposively selected cervical cancer patients receiving follow-up treatment at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia. Data were collected using semi-structured interviews and analyzed via thematic analysis. Results:The results obtained in this study indicated that women experienced a variety of physical and psychosocial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…The cost of treatments also rendered some patients’ families bankrupt with others forced to sell the assets they had to cater for such costs. Similar findings of socioeconomic disruptions as a result of the disease were reported in other studies [ 14 , 15 , 21 ]. It was also revealed that the disruption imposed by cervical cancer on social and economic aspects of patients’ life was a source of constant stress, low self-esteem, and isolation [ 14 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The cost of treatments also rendered some patients’ families bankrupt with others forced to sell the assets they had to cater for such costs. Similar findings of socioeconomic disruptions as a result of the disease were reported in other studies [ 14 , 15 , 21 ]. It was also revealed that the disruption imposed by cervical cancer on social and economic aspects of patients’ life was a source of constant stress, low self-esteem, and isolation [ 14 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Women with cervical cancer experience dissatisfaction with healthcare services, inadequate information from healthcare providers, and poor compliance with treatment regimens [ 21 , 22 ]. Studies conducted in Ghana and Ethiopia revealed that women with cervical cancer experienced health deterioration caused by illness, psychological disturbance after receiving cancer diagnostic results, and experiencing devastating symptoms of the disease [ 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study in Ethiopia, women with cervical cancer were not satis ed with care because care professionals were not supportive and caring since they did not explain all aspects of their illness. Women expressed the importance of receiving cervical cancer information from healthcare professionals to adjust to their situation [32]. Effective and sensitive communication with health professionals is a core component of cancer care [33].…”
Section: Discussionmentioning
confidence: 99%
“…Psychosexual support should address issues such as sexual distress, relationship satisfaction, and the partner's viewpoint in addition to physical sexual functioning. Moreover, it would be bene cial to provide more useful and reassuring information regarding the implications of cervical cancer for relationships and sexuality (32)(33)(34)39). Women may better handle the challenges related to sexual activity if their sexual and psychological needs are given greater consideration (27).…”
Section: Limitations the Study Andmentioning
confidence: 99%